2023
DOI: 10.1155/2023/9125265
|View full text |Cite|
|
Sign up to set email alerts
|

Human Umbilical Mesenchymal Stem Cells-Derived Microvesicles Attenuate Formation of Hypertrophic Scar through Multiple Mechanisms

Abstract: Mesenchymal stem cells and the derived extracellular microvesicles are potential promising therapy for many disease conditions, including wound healing. Since current therapeutic approaches do not satisfactorily attenuate or ameliorate formation of hypertrophic scars, it is necessary to develop novel drugs to achieve better outcomes. In this study, we investigated the effects and the underlying mechanisms of human umbilical mesenchymal stem cells (HUMSCs)-derived microvesicles (HUMSCs-MVs) on hypertrophic scar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%